An Axiological Turn in European Constitutionalism? (Polish Yearbook of International Law, 2025)
Article 2 of the Treaty on European Union (TEU), stipulating that the Union was founded on the values common to its Member States (MSs), has led to a shift towards values in the drafting, application and interpretation of EU law. This can be seen as a significant paradigm shift in the discourse on European constitutional pluralism. It represents a transition, yet not a departure, from the “Union of law” to the “Union of values”, from a Union that is neutral towards values to one that is value-friendly. This paradigm shift is especially symbolised and illustrated by the reference to values in the case law of the Court of Justice of the European Union (known as Wertejurisprudenz), the promotion of values in the EU’s international relations and policies and the use of values to legitimise EU legislation and as a criterion for reviewing and assessing the MSs’ activity, even in domains that are within their exclusive purview. A characteristic feature of the values listed in Art. 2 TEU, on which the strength and scope of their impact on the EU legal and institutional system directly depend, is the fact that they are legal values forming – as internal values – an integral part of the founding Treaties. Due to their placement within the Treaty structure, they are fundamental values, and because of the Treaty’s role as a constitutional charter, they are also foundational values. The listing of these values in Art. 2 TEU has objectified them – their substance no longer depends on individual moral beliefs. They are legal norms that are legally binding on their addressees. In the literature, Art. 2 TEU is often given the status and role of a homogeneity clause. However, with all due respect for this interpretative approach, I consider it inconsistent with both the meaning of this provision, which was intended to strengthen  the Union’s legitimacy, and with the premises of European constitutional pluralism, which safeguard and protect the pluralism of values while opposing their uniformity and hierarchisation. It seems, however, that turning values into homogenising clauses that would unify the quantitatively and qualitatively diverse MSs’ constitutional value standards – with the CJEU monitoring their compliance with as-yet undetermined EU models – and deriving particular obligations for the MSs from these values in conjunction with other Treaty provisions is taking it too far